Start-Up Ecosystem in Makassar: Determinants of Success and Challenges Faced - Fatmawaty, A. St. (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the development of the start-up ecosystem in Makassar City, focusing on the factors that influence success and the challenges faced by start-up actors. Using mixed methods, this study combines qualitative data analysis of 30 local start-ups and in-depth interviews with various stakeholders, such as start-up founders, investors, local government, as well as communities and incubation centers. The results show that access to capital, support from local government, and the quality of human resources are key success factors for start-ups, while key challenges include limited digital infrastructure and difficulty accessing broader markets. The practical implications of these findings include the need to improve access to capital through partnerships with investors and more affordable funding programs, the development of equitable digital infrastructure to support access and service quality, and human resource training to strengthen technical and managerial skills. In addition, there needs to be support to help start-ups access regional and national markets through collaboration with local governments and joint promotions, in order to expand market reach and improve the competitiveness of start-ups in Makassar. With these steps, the start-up ecosystem in Makassar can further develop and have a positive impact on the local economy